2016
DOI: 10.1177/0734242x16659922
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solid content, carbon/nitrogen ratio and food/inoculum ratio for biogas production from food waste

Abstract: Biogas production from food waste has been used as an efficient waste treatment option for years. The methane yields from decomposition of waste are, however, highly variable under different operating conditions. In this study, a statistical experimental design method (Taguchi OA) was implemented to investigate the effects of simultaneous variations of three parameters on methane production. The parameters investigated were solid content (SC), carbon/nitrogen ratio (C/N) and food/inoculum ratio (F/I). Two sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…[37,38]. Furthermore, Dadaser-celik et al have reported the significant greater contribution of solid content followed by feed/inoculum in the generation of biogas from food waste [39]. At lower total solid content, HRT increased with decrease in feed/inoculums ratio, while it decreased with increase in feed/inoculum ratio (Figs.…”
Section: Interaction Effect Of Operating Variablesmentioning
confidence: 93%
“…[37,38]. Furthermore, Dadaser-celik et al have reported the significant greater contribution of solid content followed by feed/inoculum in the generation of biogas from food waste [39]. At lower total solid content, HRT increased with decrease in feed/inoculums ratio, while it decreased with increase in feed/inoculum ratio (Figs.…”
Section: Interaction Effect Of Operating Variablesmentioning
confidence: 93%
“…In case of maximizing the biogas yield, the larger-thebetter characteristic was applied using Eq. 1 [26].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…While several investigations have tried to improve the methanogenesis step through optimization of single parameters such as temperature or pH [75,76], it is clear that operation parameters relate to each other and thus optimization study should not only focus single parameters. The methodologies which can be used to optimize and understand the relationship between temperatures, pH and ammonia concentration in the AD process are thus required.…”
Section: Optimizing the Methanogenesis Phasesmentioning
confidence: 99%